PSIX-37 Considerations for using game cameras for on-farm behavior of beef cattle. (30th November 2020) - Crites, Benjamin; Roy, Nicholas; Stamm, Clay; Sears, Brandon; Campbell, Matthew; Musen, Steven; Barnes, Jessica; Williams, Victor; Coffey, David; Lehmkuhler, Jeffrey
Abstract: On-farm studies provide an opportunity to build relationships with clientele while answering applied science questions. Further, game trail cameras are a low-cost technology that may be an alternative to visually observing livestock for behavior data. An on-farm study involving eight county Extension agents and producers investigated game cameras to capture cattle visitation to mineral feeders. Three different models of Browning game trail cameras (Prometheus Group LLC, Birmingham, AL) each with timelapse feature were utilized. A three-page document provided background and methodology for the study. Details for placement of the trail camera were provided to provide consistency across farms. Cameras were pre-programmed to settings for image capture. A video for camera setup was also provided in the event that cameras reset to default settings due to battery failure. Timelapse feature was utilized providing image capture from sunrise to sunset at 2 min intervals. Several observations were noted to improve data capture in the future. Differences existed in battery utilization between camera models with one model only capturing images for approximately 2 of the 7 d periods while others had more than 80% battery life remaining after 7 d. Cameras were to be oriented facing south to avoid sun glare. Sun glare occurred at sunrise on most cameras and was particularly bad when dew was present on the camera lens. Mineral feeders need to be secured in place as livestock may move feeders out of the frame of the images captured. Still photos are insufficient in assessing behavior and short video clips are expected to improve interpretation especially when multiple animals visit the feeder at the same time. Utilization of human observation was not useful unless observation was performed at sunrise. Game trail cameras have the potential to be a cost-effective tool in capturing on-farm data of cattle behavior.